Innovative Approaches in Statistics Education: The Role of Technology Explored through Meta-Analysis - Sa'idah, Nusrotus (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
This meta-analysis examines the impact of technology in statistics learning, comparing experimental and control groups across 34 studies, resulting in 55 effect sizes. The random effects model revealed a significant standardized mean difference (gRE = 0.50, 95% CI [0.35, 0.64], p < 0.01), indicating a positive effect of using technology in statistics courses. Heterogeneity was high (I² = 94.3%), and publication bias was initially detected; however, it was addressed by removing 21 outlier studies. The analysis revealed no significant differences based on country; however, technology type had a significant effect. These findings suggest improved student outcomes, warranting further investigation.